PEMANFAATAN TUMBUHAN PANGAN DAN OBAT OLEH MASYARAKAT DI DUSUN PALUTUNGAN, DESA CISANTANA, SEKITAR TAMAN NASIONAL GUNUNG CIREMAI - Putri Prica Salsabila; Ervizal A.M. Zuhud; Siswoyo . (Media Konservasi, 2014)
The utilization of plants for fulfill food requirement and healing are the oldest medicinal in the world. Every culture in the world has specific traditional medicine system and in every region has found many plants that can be used as food and medicine. The objective of this research is to study of diversity and utilization food plant and medicine by the people of Palutungan District, Cisantana Village. This research implemented on January until June 2014. Results of the study showed that the number of food plant species used by the Dusun Palutungan was 46 kinds and 56 species for medicinal plants. The most effective ways for utilization food plants was cooked, while the most effective ways for utilization medicinal plants was boiled.Keywords : Biodiversity, Food plants, Medicinal plants, Palutungan District, and Utilization.